PROBLEMATIC OF REFUSAL THE APPLICATIONS FOR SUSPENSION OF DEBT PAYMENT OBLIGATIONS FOR SUBSIDIARIES OF STATE OWNED ENTERPRISES - Mhd Edwin Prananta Surbakti; Sunarmi Sunarmi; Budiman Ginting; Dedi Harianto (NOMOI Law Review, 2023)
The legal position of SOE subsidiaries does not have legal certainty, giving rise to multiple interpretations. There are multiple interpretations in statutory regulations and jurisprudential decisions, namely the decisions of the Supreme Court Number: 21P/HUM/2017 and the decision of the Constitutional Court Number 01/PHPU-PRES/XVII/2019. The approach used is the law approach, and the case approach. Source of data used in the form of secondary data. Data collection techniques and tools used were library research, field research, document studies and interview guides. Data analysis was carried out qualitatively. The results showed that the BUMN subsidiary, namely PTPN I, was a holding structure of PTPN III, which declared the status of a BUMN, due to direct state capital participation in the form of 1 Series A Dwi Warna share. In accordance with PP No. 72 of 2016 that a subsidiary in the holding structure, namely PTPN I, receives a special assignment from the government in the form of a Public Service Obligation (PSO), Management Rights (HPL) and the Partnership and Community Development Program (PKBL), Based on Article 2A Paragraph (7) ) a BUMN subsidiary in a holding structure, namely PTPN I, is treated the same as a BUMN. As a result, creditors are not authorized to apply for bankruptcy and PKPU, but are the Minister of Finance in accordance with Article 223 in conjunction with Article 2 paragraph (5) of Law Number 37 Years.